Educational Financing Management in Improving the Quality of Education at MTS Walisongo Pontianak - Wahyuni, Efa Sri; Wicaksono, Luhur; Ulfah, Maria (Jurnal Ilmiah Mandala Education (JIME), 2024)
Education financing is one of the central systems in education. This study aims to find out about financing to support the implementation of education. This research is a descriptive research with a qualitative approach. The results of the study show that the use of education financing is oriented towards the head of educational operational financing that supports improving the quality of education that is right on target by fulfilling the school financial management governance system that must be understood in the implementation of education financing, namely the concept of education budgeting, classifying activities, determining standardization, and determining costs unit in education budgeting. Education financing management has three important stages, namely planning, implementation stage and evaluation (evaluation) stage. These three stages when applied to financial management are the financial planning (budgeting) stage, and the implementation (accounting) stage, and the appraisal or auditing stage. With an education financing management system, it is hoped that it will be able to support, guarantee the development of the quality and quality of education and the process of organizing teaching and learning activities.